The management of the Sekolah Orang Tua Hebat program for strengthening school–parent collaboration - Dwi Wahyu Rachmawati; Muhamad Sholeh; Ainur Rifqi; Amrozi Khamidi; Karwanto Karwanto; Mohammad Syahidul Haq (Rafandha Press, 2025)
Background: Collaboration between schools and parents is a key factor in the success of children’s education. However, its implementation still faces challenges such as low parental involvement, high expectations placed on schools, and limited adjustment of programs to family characteristics. Purpose: This study aims to analyze the management of the Sekolah Orang Tua Hebat (SOBAT) program in strengthening school–parent collaboration at SMPN 1 Singojuruh, Banyuwangi, with a focus on the functions of planning, organizing, implementing, and controlling (POAC). Method: The research employed a qualitative approach with a case study design conducted over a 4-month period at SMPN 1 Singojuruh, Banyuwangi. Five research informants (1 principal, 2 facilitators, 2 parents) were selected through purposive sampling. Data were collected through in-depth interviews, observations, and document analysis, then analyzed interactively using the Miles, Huberman, and Saldana model involving data reduction, data presentation, and conclusion drawing. Data validity was ensured through source triangulation, method triangulation, member checking, and prolonged engagement with informants. Findings: The results indicate that program planning was carried out participatively by involving the Education Office, school principals, teachers, and parents, while considering flexible scheduling according to families’ socio-economic conditions. Program organization was characterized by adaptive structures, clear task distribution, and intensive facilitator training. Implementation applied the DEF method (Dialogue, Education, Facilitation) and 16 comprehensive parenting modules, enabling peer learning and empowering parents as learning resources. Program control was conducted participatively through direct observation, periodic questionnaires, and parental involvement in evaluation. The study concludes that the integrated application of POAC functions strengthens school–parent collaboration, increases family involvement in children’s education, and supports alignment of parenting patterns between schools and families.